A decade of human security global governance and new multilateralisms - MacLean, Sandra Jean 1947-; Black, David R. (David Ross) 1960-; Shaw, Timothy M. (Global security in a changing world, 2006)
Investigates innovations in the advancement of the human security agenda over the years and identifies themes and processes around which consensus for future policy action might be built. This book elaborates the debates regarding the human security agenda, considers prospects and projects for the advancement of human security, and more.